2015
DOI: 10.1038/npjmgrav.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in adaptive immunity persist during long-duration spaceflight

Abstract: Background:It is currently unknown whether immune system alterations persist during long-duration spaceflight. In this study various adaptive immune parameters were assessed in astronauts at three intervals during 6-month spaceflight on board the International Space Station (ISS).AIMS:To assess phenotypic and functional immune system alterations in astronauts participating in 6-month orbital spaceflight.Methods:Blood was collected before, during, and after flight from 23 astronauts participating in 6-month ISS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
175
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(197 citation statements)
references
References 32 publications
18
175
1
3
Order By: Relevance
“…Our results are in accordance with previous NASA studies that demonstrate International Journal of Aerospace Engineering that even bones are affected over the course of long-term missions by loss of their total hip bone mass [14]. Moreover, our data add information to the list of known effects of space flights on the human body during long-duration missions such as muscle atrophy, bone demineralization, altered immune function [15,16], cardiovascular system dysfunction [17,18], and also alterations in sleep function [19]. A significant amount of data on the decrease in the performance of various groups of muscles has been collected from astronauts flying from 1989 to 1995 in NASA's orbiters or Russian capsules [20].…”
Section: Discussionsupporting
confidence: 80%
“…Our results are in accordance with previous NASA studies that demonstrate International Journal of Aerospace Engineering that even bones are affected over the course of long-term missions by loss of their total hip bone mass [14]. Moreover, our data add information to the list of known effects of space flights on the human body during long-duration missions such as muscle atrophy, bone demineralization, altered immune function [15,16], cardiovascular system dysfunction [17,18], and also alterations in sleep function [19]. A significant amount of data on the decrease in the performance of various groups of muscles has been collected from astronauts flying from 1989 to 1995 in NASA's orbiters or Russian capsules [20].…”
Section: Discussionsupporting
confidence: 80%
“…It is also interesting that the highest concentration of reported events occurred early within the 6-month mission durations. While the slope of immune alterations during spaceflight is still largely unknown, the literature to date generally finds that alterations persist for the duration of a 6-month orbital spaceflight 25. We anticipate upcoming investigations on board the ISS will shed further light on the complexities of immune adaptation during flight, and planned 1-year mission durations will improve our understanding regarding the kinetics of these alterations.…”
Section: Discussionmentioning
confidence: 95%
“…Humoral immunity may also be affected by spaceflight, as animal studies have indicated that the somatic hypermutation process responsible for diversification of antibody binding sites was reduced during spaceflight 23. Recent data collected on board the Space Shuttle and International Space Station (ISS) confirms that human immune dysregulation is indeed an in-flight phenomenon, and not merely a post-flight stress response to landing and readaptation following deconditioning 24,25…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, carbon dioxide levels and humidity are well controlled in space shuttles5657. A project examining immune parameters, i.e., peripheral leukocyte distribution, T-cell function, virus-specific immunity, and mitogen-stimulated cytokine production profiles, in twenty-three astronauts revealed that the immune alterations persist during long-duration (6 month) spaceflights58. Immune alterations are likely to be critical factors in the changes in homeostasis occurring in astronauts.…”
Section: Discussionmentioning
confidence: 99%